2019
DOI: 10.3390/w11051054
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impacts of Climate Change, Coal Mining and Soil and Water Conservation on Streamflow in a Coal Mining Concentrated Watershed on the Loess Plateau, China

Abstract: The streamflow has declined significantly in the coal mining concentrated watershed of the Loess Plateau, China, since the 1970s. Quantifying the impact of climate change, coal mining and soil and water conservation (SWC), which are mainly human activities, on streamflow is essential not only for understanding the mechanism of hydrological response, but also for water resource management in the catchment. In this study, the trend of annual streamflow series by Mann-Kendall test has been analyzed, and years sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
6
0
10
Order By: Relevance
“…In this study, only monthly rainfall was used as climatic input to the model. Rainfall intensity and rainfall duration greatly influenced the amount of runoff, but they were not included in this SCS-CN model [68]. The rainfall erosivity calculated using the Wischmeier model based on monthly rainfall was higher than that calculated using a half-month model based on daily rainfall.…”
Section: Observed and Predicted Soil And Water Erosionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this study, only monthly rainfall was used as climatic input to the model. Rainfall intensity and rainfall duration greatly influenced the amount of runoff, but they were not included in this SCS-CN model [68]. The rainfall erosivity calculated using the Wischmeier model based on monthly rainfall was higher than that calculated using a half-month model based on daily rainfall.…”
Section: Observed and Predicted Soil And Water Erosionmentioning
confidence: 96%
“…Therefore, more heavy rainfall and runoff events in the rainy season will result in more soil and water erosion. However, climate change may contribute to 14.3-31% of streamflow change in north China [74,75], while human activities, such as land-use change and SWCPs, would also be an important factor influencing runoff and soil erosion [68,76]. The reduction rates of surface runoff and soil erosion varied among experimental plots with different SWCPs (Figure 2).…”
Section: The Effect Of Different Swcps On Soil and Water Conservaionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research works were carried out to understand the variability of streamflows due to climate change [10][11][12][13][14][15] with mixed results in the streamflow variability, depending on the region and season. For instance, a decrease in annual streamflow was observed [5,16].…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggest an increasing trend in streamflow without the effect of dams, while the inclusion of a few major dams resulted in decreased river streamflow of 6% to 15%, possibly due to irrigation diversions and climate change. Guo et al [2] quantified the impacts of climate change, coal mining, and soil and water conservation on streamflow in a coal mining concentrated watershed on the Loess Plateau, China. They found that relative to the baseline period, i.e., 1955-1978, the mean annual streamflow reduction in 1979-1996 was mainly affected by climate change, which was responsible for a decreased annual streamflow of 12.70 mm (70.95%).…”
Section: Introductionmentioning
confidence: 99%